Slight damage of the great green bush-cricket (Tettigonia viridissima) (Orthoptera: Tettigoniidae) in some Hungarian maize fields - Bozsik, András (Acta Agraria Debreceniensis, 2015)
Characteristic cricket damage was observed in two maize fields in northern Hungary, at Máriabesnyő, a district of Gödöllő. The damage level of the two fields did not differ significantly and continual monitoring of field1 showed also a stable infestation level. T. viridissima nymphs and a female were found and observed as feeding on maize plants. The crickets must have disappeared after 18.07. because no more fresh damage was observed after this date. The chewing’s number about on one and two % of the examined plants amounted one and six a plant and their size was between one and eight cm2. This infestation was quite little and might have caused apparently no yield loss. Compared this damage of T. viridissima with former Hungarian experience, this was the usual negligible damage despite the explicit draught in July and August 2015. As regards the global warming, orthopteran damage may be more obvious in the future.